The Historical Development of Japanese Investment in Malaysia, 1971 â 1980 - Iqbal, Uqbah; Hussin, Nordin; Seman, Ahmad Ali (SUSURGALUR, 2014)
ABSTRACT: Malaysia-Japan economic relations continued during the administration of Tun Abdul Razak (1970-1975); and Malaysia-Japan economic relations strengthened during the administration of Tun Hussein Onn (1976-1980). This study discusses the historical development of Japanese investment in Malaysia between 1971 and 1980. The research is based on the examination method of the resources available in the library and the National Archives of Malaysia. The objective of the study is to see the patterns on the Japanese investment in Malaysia after the implementation of the NEP (New Economic Policy) in 1971. It is also the period of Tun Abdul Razak and Tun Hussein Onn administration. After 1970, Japanese investors began investing through joint venture with government organizations, such as the National Corporation Limited (PERNAS), Majlis Amanah Rakyat (MARA), and the Federal Land Development Authority (FELDA). This is in line with the NEP policy that emphasizes the participation of Bumiputera (Malay citizen). These agencies represent Bumiputera participation. Japanese investment in this period was in labour-intensive industries that involve cheap labour, raw material processing, and trade-related investment.KEY WORD: Investment, Japan, Malaysia, New Economic Policy, economic relations, joint ventures, and Bumiputera participation.IKHTISAR: âSejarah Perkembangan Pelaburan Jepun di Malaysia, 1971 â 1980â. Hubungan ekonomi Malaysia dan Jepun diteruskan semasa zaman pentadbiran Tun Abdul Razak (1970-1975); dan hubungan ekonomi Malaysia dan Jepun diperkukuhkan lagi semasa zaman pentadbiran Tun Hussein Onn (1976-1980). Kajian ini membincangkan sejarah perkembangan pelaburan Jepun di Malaysia antara tahun 1971 hingga 1980. Kaedah kajian yang digunakan adalah berdasarkan kaedah penelitian terhadap sumber-sumber yang diperolehi di perpustakaan dan Arkib Negara Malaysia. Objektif kajian ialah melihat corak pelaburan Jepun di Malaysia selepas perlaksanaan DEB (Dasar Ekonomi Baru) pada tahun 1971. Ia juga merupakan tempoh pentadbiran Tun Abdul Razak dan Tun Hussein Onn. Selepas tahun 1970, pelabur Jepun mula melabur melalui usahasama dengan organisasi kerajaan, seperti Perbadanan Nasional Bhd (PERNAS), Majlis Amanah Rakyat (MARA), dan Lembaga Kemajuan Tanah Persekutuan (FELDA). Ini selaras dengan dasar DEB yang menekankan kepada penglibatan golongan Bumiputera. Agensi-agensi ini mewakili penyertaan Bumiputera. Pelaburan Jepun dalam tempoh ini adalah dalam industri berintensif buruh yang mengambil tenaga buruh murah, pemrosesan bahan mentah, dan pelaburan berkaitan perdagangan.KATA KUNCI: Pelaburan, Jepun, Malaysia, Dasar Ekonomi Baru, hubungan ekonomi, usahasama, dan penyertaan Bumiputera.Â Â Â Â About the Authors: Uqbah Iqbal is a Ph.D. Student at the School ofÂ History,Â Politics and Strategy, Faculty of Social Sciences and Humanities UKM (National University of Malaysia), 43650 Bangi, Selangor Darul Ehsan, Malaysia; and Prof. Dr. Nordin Hussin & Dr. Ahmad Ali Seman are Lecturers at the School ofÂ History,Â Politics and Strategy UKM Bangi, Malaysia. Their e-mails address are: uqbah@siswa.ukm.edu.my, nordin@ukm.edu.my, and aasw@ukm.edu.myHow to cite this article? Iqbal, Uqbah, Nordin Hussin & Ahmad Ali Seman. (2014). âThe Historical Development of Japanese Investment in Malaysia, 1971 â 1980â in SUSURGALUR: Jurnal Kajian Sejarah & Pendidikan Sejarah, Vol.2(2), September, pp.233-250. Bandung, Indonesia: Minda Masagi Press and UBD Bandar Seri Begawan, Brunei Darussalam, ISSN 2302-5808.Â Chronicle of the article: Accepted (August 13, 2014); Revised (September 5, 2014); and Published (September 24, 2014).